Defending The Country on The Movement of The Younger Generation in Lafran Pane’s Perspective - Azizah, Umi; Djono, Djono; Musadad, Akhmad Arif; Ariwidodo, Eko (KARSA Journal of Social and Islamic Culture, 2021)
This research discusses the defensive attitude of the younger generation, especially the younger generation of muslims, based on Lafran Pane’s thoughts. Lafran Pane is one of the hero figures in Indonesia who had a significant influence on maintaining Indonesia's independence. This research aims to determine and understand Lafran Pane’s thoughts on defending the country by the younger generation, especially the younger generation of muslims in Indonesia. The method used in this research is the descriptive qualitative research method. This study found that Lafran Pane emphasized the young age to maintain Indonesian independence by returning to the Islamic teachings and practicing them in all activities. He has reformed thoughts in various fields, created a new education system, made Islamic and Indonesian-ness the starting point for the movement.